Determinasi Religiusitas, Lokasi, dan Faktor Sosial dalam Pemilihan Program Studi Bahasa Arab di STIM Surakarta - Romadhon, Farkhan Nur; Putra, Sudarmadi; Budiriyanto, Anis; Winanto, Edy; Widodo, Joko (Lembaga Sosial Rumah Indonesia, 2023)
This study aims to analyze the influence of religiosity, location, and social factors on students' choices in choosing the Arabic Language Study Program at STIM Surakarta. The approach used is qualitative with a case study method. Data were collected through in-depth interviews, observations, and documentation. Data analysis was carried out using a thematic approach to understand the influence of the three factors. The results of the study show that student religiosity is the main driver in choosing this study program, supported by the strategic location of the campus and social factors such as family and community support. This study provides insight for study program managers to design strategies to increase attractiveness based on these factors. On the other hand, the religiosity factor has a smaller influence than the other two factors.